It's not the end: destigmatising education-based stigma in Singapore - Sim, Shanna Si Lei (Nanyang Technological University, 2024)
Defined as the discrimination based on the educational status and the affiliation to the education institution, education-based stigmatisation is rooted in the social process of academic streaming within the education system where the individual is ascribed a stigma on the basis of their enrolment into the academic institution. In Singapore, the Institute of Technical Education has long been negatively perceived as being associated with less well-educated individuals and delinquency – this public perspective arises due to a combination of factors, such as the global socio-historical roots of vocational education and training, the valuation of the knowledge worker, academic streaming and sorting of students in Singapore, media reports of delinquents enrolled in the institution, as well as the pervasiveness of meritocratic ideology in Singapore’s social structure. As a response to the stigma, top-down efforts initiated by the institution and education reforms aim to destigmatise the collective and the institution have resulted in media reports of positive deviances. These individuals accounts reported in the media are presented as “ITE success story” a narrative founded on the principles of meritocracy in the individual education-career trajectory. To understand the phenomenological experiences of those in the lower stratum of the education system, who are educationally stigmatised, the present study uses semi-structured and focus group discussions to explore the school-to-work transitions and the individual responses to the ideological beliefs and practices of meritocracy embedded within social structures, social interactions and the self. It found that in response to ascribed stigma, individuals engaged in various strategies in order to manage the self and their social identity, these included resisting and overcoming stigma through the reinterpretation of experiences. In addition, the study also found that the porous nature of the Singapore education system resulted in an increasingly differentiated pathway among participants where individuals were motivated to pursue their passion and thus, aligning the education-career trajectories to their identity. In the process of aligning their education-career trajectories, individuals exercised reflexivity in their social position, the identity capital available, and the opportunity structures, thus engaging in the navigation of the social structure.